Curricular flexibilization as a feasible mechanism of inclusion of students with disabilities: perception of the elementary school teachers in the city of Acopiara-CE (Research, Society and Development, 2022)
This study aims to understand teachers' perceptions of curriculum flexibility and whether they experience it in their practice with students with disabilities. The exploratory study is based on a qualitative approach and heard, through an electronic questionnaire, seven elementary school teachers from the municipal public network of the city of Acopiara-Ce. Data analysis highlighted the challenges experienced by teachers in their work contexts, with classrooms with a high number of students with disabilities, fragility in teacher training, inadequate physical structure, difficulty in pedagogical accessibility and in the structure of support staff. It also revealed that the participants have superficial knowledge about curricular flexibility, although they say that they knew the term in their initial or continuing education. The study points to the importance of further studies on curricular flexibility, at the same time it reveals the need to contemplate in teacher training on the subject, which is so important for the construction of a more inclusive teaching performance.